Impact of Digital Sociology on Land Usage in New Cities - AbdulKareem AbdulGani , Researcher. Hala; Shakir Khudair Al Kinani , Prof. Dr. Amir (Basra studies journal, 2023)
Digital sociology considered to be a new concept in the field of digital social science, it explains the behavioral mechanism of modern society. In presence of digital technological forces, it has smart tools and it is involved with different aspects of life, like (educational, economic, social, political aspects) in accordance to digital sociological data. The effects of the new behavior of society on the new city planning especially urban land usage by incorporating the financial and digital realities in new city planning and within what would be called intelligent cities. In comparing it to weak acceptance by traditional cities to new digital sociology behavior data to society, the study reached the conclusion of the importance of direction toward urban land usage suitable for new society’s requirements.